(untitled) (The Chittagong University Journal of Arts & Humanities, 2026)
Abstract: Generosity is a vital precept in Islam. Islam promotes generosity and suggests adopting generosity in its all aspects including religious practices, rituals, attitudes, transactions, behavioural issues, etc. Islam strongly opposes extremism in any of its phases. Some acts of extremism by a tiny group of people leave scope for the enemies of Islam to relate extremism with Islam. Therefore the purpose of the study is to examine the issues in the light of Shariah Texts whether Islam is associated with extremism, how values of generosity and moderation in Islam oppose extremism and how far it is rational to link extremism with Islam. The data will be assessed using analytical and descriptive approaches. The findings reveal that Islam is a religion that promotes generosity in all its aspects, rejects extremism in those all and has no farthest relation with extremism. This study will help both the supporters and non-supporters of Islam apprehend the true essence of Islam in general and bona fide Muslims. In particular, reject extremism in all aspects of life.